(untitled) (ETNOSIA : Jurnal Etnografi Indonesia, 2025)
Indonesia’s linguistic diversity is under threat, with a steady decline in the use of local languages despite constitutional protections. In urban centers like Semarang, dialects such as Ngapak face social stigma, leading migrant students to adjust their speech patterns. Unlike previous studies that focused primarily on speech strategies, this study examines deeper sociolinguistic issues, including dialect stigma and language-based marginalization. Using qualitative case study approach, this study was conducted in Semarang Central Java. Data were collected through semi-structured interview with 20 participants, observation, social media analysis, and online surveys. They were then categorized using the CAT framework and compiled into a comprehensive research report. The findings show that stigmatization is rooted in historical, institutional, and popular factors. Ngapak students employ convergence, divergence, and maintenance strategies depending on context and interlocutor, with a stronger tendency toward convergence. These strategies influence how they are perceived and socially integrated. In conclusion, their communication strategies reflect their efforts to navigate stigma, negotiate identity, and maintain linguistic pride within a linguistically diverse campus environment.